Traditional practices in newborn and infant care: A public health issue - El Ajroudi Ouafae; Razzok El Mahdi; Amrani Rim (E3S Web of Conferences)
During the postnatal period, mothers are destabilized by the imbalances that accompany this phase of their children's lives. The search for solutions leads them to substitute newborns medical care interventions with traditional home-based practices, which are characterized by their dangers for the health of young children. This issue prompts our interests to explore traditional practices within Moroccan context, particularly in rural and urban areas of the Eastern Moroccan region. The study is based on a quantitative approach and involves 422 mothers of children under the age of one. Using an online questionnaire, the study identifies the main factors influencing the adoption of traditional care by Moroccan mothers. The observations show a high prevalence of traditional dietary (63.5%) and body care practices (56.9%), with specific trends and notable differences between rural (89.5) and urban (70.0%) areas, as well as social, cultural and economic factors contributing to the persistence of these practices among Moroccan mothers. The results report a significant association between the practice of dietary care and place of residence (p<0.001), level of education (p=0.030), professional occupation (p=0.004) and access to healthcare facilities (p=0.022) and a significant association also between body care and place of residence (p<0.001), level of education (p=0.003), professional occupation (p<0.001) and access to healthcare facilities (p=0.047). The results suggest that these traditional practices, which are still maintained due to deeply rooted ancestral cultural beliefs and limited access to modern healthcare in some areas, require the implementation of a health policy based on effective intervention strategies to achieve the sustainable development goals in Morocco.